Case Report: Lesion network guided transcranial direct current stimulation targeting treatment refractory hallucinations and delusions: a traditional and accelerated stimulation case study - Raymond, Nicolas; Trotti, Rebekah; Lizano, Paulo (Frontiers in Psychiatry, 2025)
Transcranial electrical stimulation (tES) has been shown to reduce symptoms related to psychosis, especially positive symptoms such as auditory hallucinations (AH). However, there are time and transportation burdens that fall on patients since typical tES treatments are performed over 5 days in-clinic and consist of twice daily tES sessions. Evidence suggests that accelerated protocols (repeated number of tES sessions over fewer days) may have similar efficacy as traditional 5-day tES protocols. Moreover, few investigations have sought to target novel brain regions linked to AH, such as those identified by advanced neuroimaging studies that identify causal neural substrates that manifest AH. Here, we report on a 62-year-old woman with persistent treatment-resistant AH. We performed two tES treatment protocols (a 5-day traditional protocol and a 2-day accelerated protocol) targeting a brain region that has been causally linked to the manifestation of AH, the right superior temporal sulcus (rSTS). Both traditional and accelerated protocols resulted in a decrease in AH and distinct electroencephalogram (EEG) changes that tracked with symptom changes.